Behavioural Reasoning Theory Perspectives: Hospitality Accounting System Adoption - Dwiyanti, I Gusti Kadek Anggiriska; Dewa Gede Wirama (Jurnal Akuntansi, 2024)
This study delves into the behavioural intention to adopt Hospitality Accounting Systems (HAS) in Bali's villa accommodation sector, employing the Behavioral Reasoning Theory (BRT) framework. Through a representative sample of 363 villa owners or managers, utilising the PLS-SEM technique, it explores how personal values, reasons for and against, and attitudes influence HAS adoption intentions. The findings underscore the significant impact of attitude on adoption intentions, with values significantly affecting attitude and reasons for and against. Interestingly, while reasons for directly influence intention, reasons against have the opposite effect. Future research avenues could explore additional factors influencing technology adoption and delve into the long-term implications of technology integration on organisational performance and user satisfaction. This study enriches theoretical frameworks and offers actionable insights for enhancing technology adoption in the hospitality industry and beyond.